Discourse Markers Used in Argumentative Texts of English Department Student in Bali - Ayu Dhyana Andika Mulia Putri, Desak; Agung Sri Rwa Jayantini, I Gusti (CV. Multi Kreasi Media, 2024)
Discourse markers improve writing quality and text comprehension. This paper aims to shed lighter on how to assess students' knowledge of Discourse Markers. The purpose of this study was to determine the ability of students to compose or opinions using discourse markers as a support in conveying their opinions and arguments. Furthermore, the purpose of this study is to demonstrate the significance of using discourse markers in determining the quality of written work. The qualitative method with observation technique was used in this study, and the data collected were 10 argumentative essays written by sixth semester students on the topic of bird conservation. Following the collection of data, the researcher began to observe all of the data by reading all of the essays, identifying discourse markers, and finally classifying discourse markers based on the existing types based on Fraser (1999) and Martinez (2004) theories. Conclusive markers, contrastive markers, elaborative markers, exemplifier markers, inferential markers, and reason markers are all found in the essays. The most common types are elaborative markers, which have a total of 221 occurrences and discovered some misused in the use of appropriate discourse markers While participants demonstrated an awareness of using discourse markers to construct coherent compositions, the study concludes that there are areas where they can enhance their ability to use discourse markers effectively and appropriately to improve and logically connect their writing.